Energy Loss Savings Using Direct Current Distribution in a Residential Building with Solar Photovoltaic and Battery Storage - Patrik Ollas; Torbjörn Thiringer; Mattias Persson; Caroline Markusson (Energies, 2023)
This work presents a comparison of alternating current (AC) and direct current (DC) distribution systems for a residential building equipped with solar photovoltaic (PV) generation and battery storage. Using measured PV and load data from a residential building in Sweden, the study evaluated the annual losses, PV utilization, and energy savings of the two topologies. The analysis considered the load-dependent efficiency characteristics of power electronic converters (PECs) and battery storage to account for variations in operating conditions. The results show that DC distribution, coupled with PV generation and battery storage, offered significant loss savings due to lower conversion losses than the AC case. Assuming fixed efficiency for conversion gave a 34% yearly loss discrepancy compared with the case of implementing load-dependent losses. The results also highlight the effect on annual system losses of adding PV and battery storage of varying sizes. A yearly loss reduction of 15.8% was achieved with DC operation for the studied residential building when adding PV and battery storage. Additionally, the analysis of daily and seasonal variations in performance revealed under what circumstances DC could outperform AC and how the magnitude of the savings could vary with time.